Insights on Effective Complementary Strategies in the Management of Urinary Tract Infections - Gandhi, Shweta; Shah, Priya; Goyal, Rajat; Gautam, Rupesh K; Chopra, Hitesh (Scripta Medica, 2024)
Urinary tract infections (UTIs) are common health issues that occur frequently in both women and men. These infections occur in the urinary tract, leading to discomfort and potential complications. Prompt medical attention is essential to diagnose and treat UTIs effectively. Aim of this research was to provide an overview of effective complementary strategies in the management of UTIs. This review paper focuses on the current and future treatment strategies for UTI infections. Various natural remedies have been investigated as potential complementary therapies to enhance health outcomes for UTI patients. The efficacy of frequently employed natural products, including cranberry juice/extracts, ascorbic acid, hyaluronic acid, probiotics and multi-component formulations designed for the treatment and prevention of UTIs, has been explored. The probiotics serve to break down food and increase our immunity. Usually, multiple doses of antibiotics are used to treat these infections, but there are many side effects and bacterial resistance rates are increasing. Complementary UTI management strategies, including effective dietary regimens and new formulations, are attaining approvals. Drinking liquids daily significantly suppresses UTI infections. Incorporating daily consumption of cranberry juice may still be regarded as a viable complementary strategy to aid in the management of UTI infections.